Market power and vertical and horizontal integration in the maritime shipping and port industry - Eddy Van de Voorde; Thierry Vanelslander (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2008)
The maritime sector is undergoing constant change, as is particularly apparent in the shift in competition that has unfolded in recent years. Whereas in the past shipowners and ports used to compete with one another, the competitive struggle is now increasingly unfolding at the level of logistics chains. Today, market players are selected not so much for their stand-alone competitiveness, but on the basis of whether or not they belong to a successful maritime logistics chain. This explains why certain market players are continuously trying to gain greater control over these chains, including through vertical and horizontal alliances, mergers and acquisitions. This contribution considers in greater detail these concerted efforts to increase market power through extensive integration. First, we deal with the competitive shifts that have occurred in the port and maritime arena. Subsequently, we look at the strategic behaviour exhibited by the main market players (shipowners, terminal operating companies, port authorities, logistics service providers, etc) and analyse their objectives. Finally, we assess the consequences of the strategies pursued in the context of the anticipated future scenarios.
Keywords: 330